Des artefacts ironiques ? Relectures de La Possibilité d’une île de Michel Houellebecq - Simon Bréan (ReS Futurae)
The Possibility of an Island is a sophisticated display of literary artefacts, confronting a contemporary Frenchman autobiography to commentaries by post- human clones living two thousand years in the future. This paper studies how Michel Houellebecq uses these artefacts to establish, then destabilize his novel’s admissibility, in order to have the reader look into a real form of immortality in the present rather than in the future, in an approach both ironical and respectful toward science fiction.